Determinanty zdrowia wyznacznikiem innowacyjności produktu żywnościowego - Cebulak, Tomasz (The Health Determinants as Innovation Factors of Food Product, 2006)
The growth of quality of life should go in side the health-nutrition value. However the existing wholesome situation of society shows the treading trend backward. Therefore also the health-nutrition innovations they become with necessity. Test of the respondents' typology in article was undertaken in dependence from criterions of value of health. The results of research in support and they permitted the factor analysis on singling out three component main "the life optimists", "the health ascetics", and "the health minimalis".
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1116, s. 36-43